Clinical impact of genomic analysis in children with B-acute lymphoblastic leukemia: A pilot study in Slovakia - Vaska, A; Makohusova, M; Plevova, K; Skalicka, K; Cermak, M; Chovanec, F; Fabri, O; Svec, P; Kolenova, A (Neoplasma, 2019)
Acute lymphoblastic leukemia (ALL) belongs to a genetically heterogeneous disease associated with a wide range of chromosomal and molecular changes. Determining these changes at the time of diagnosis can help the therapeutic decision, and contributes to the prediction of patients' clinical outcomes. A part of B-ALL (B-other) lacks cytogenetic abnormalities with clinical relevance for prognosis. Our first goal was to retrospectively review genetic results of patients from 2013-2017 and identify number of B-other patients in Slovak population. The second goal was to implement single nucleotide polymorphism (SNP) array analysis to improve the diagnosis and risk stratification. In this study we reviewed 133 B-ALL patients. We found that nearly 40% of them (52 cases) belonged to the B-other ALL group. Eighteen B-other ALL patients were subjected to the analysis using SNP-array. Overall, we identified 126 cytogenomic changes and in 4 patients the SNP array revealed clinically relevant markers of adverse prognosis and high relapse risk. Integrating identified genetic changes into clinical practice can bring improvement of prognosis assessment for children with ALL in Slovakia.
Keywords: Slovenská republika; pilotní projekty; Child; Pilot Projects; jednonukleotidový polymorfismus; genomika; akutní lymfatická leukemie; retrospektivní studie; Polymorphism, Single Nucleotide; Prognosis; Humans; Genomics; lidé; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Retrospective Studies; dítě; prognóza; Slovakia